Scientometric Analysis of Multifunctional Flux Cored Welding Wire - Kim, Hwan-Tae; Kil, Sang-Cheol (Asian Journal of Chemistry, 2013)
The flux cored arc welding which uses a tubular electrode containing a flux rather than a solid electrode and which is a type of semi-automatic arc welding process is widely used in the welding of ships, offshore structures, steel structural building. As flux cored arc welding in the modern industries is placing stringent demands on the manufacturing techniques and performance requirements, the multifunctional flux cored welding wires with high quality and efficiency are developed for the production of good welds and this has led to an increasing attention in the development of multifunctional flux cored welding wires. This paper covers the scientometric analysis of the multifunctional flux cored welding wires which is based on the published research works in the 'flux cored welding wires' obtained from the Korea Institute of Science and Technology Information’s database, Web of Science System and deals with the details of the background data of the flux cored welding wire technology.